Medial Rectus Tendon Elongation with Bovine Pericard (Tutopatch®) in Thyroid-Associated Orbitopathy: A Long-Term Follow-Up including Oculodynamic MRI - Monika Wipf; Britt-Isabelle Berg; Anja Palmowski-Wolfe (Journal of Ophthalmology)
Introduction. To assess long-term efficacy of bimedial rectus tendon elongation with Tutopatch in thyroid-associated orbitopathy (TAO). Materials and Methods. Retrospective chart review of 5 patients with TAO undergoing bimedial rectus recession with Tutopatch tendon elongation between 2009 and 2015. We analyzed horizontal squint angles, motility, field of binocular single vision, dose effect of surgery, and when possible oculodynamic MRI (OD-MRI). Dose effect and motility were compared to 4 TAO patients with conventional bimedial recession. Results and Discussion. In the Tutopatch group, preoperative angles ranged from 14 to 120∆ (prism diopters) at distance and 12–120∆ at near. Mean dose effect was 3.63∆/mm for the distance and 3.43∆/mm for the near angle. All patients were orthotropic at final FU (ranging from 1 to 10 years). OD-MRI showed the elasticity of Tutopatch. In the conventional recession group, preoperative angles ranged between 18 and 35∆ at distance and 12–33∆ at near. At final FU, 2 patients had reverted to their underlying microesotropia <2∆, 1 patient was orthophor, and one was reoperated for a remaining esotropia of 14∆. Dose effect was 2.95∆/mm for the distance and 2.18∆/mm for the near angle. Motility improved in both groups even after 3 months. Conclusions. Dose effect for medial rectus recessions with Tutopatch in TAO was higher than previously reported, presenting a good alternative to treat large squint angles while preserving good motility.